Legal Aspects of Telemedicine Health Services in the Perspective of Health Law in Indonesia in the Digital Era - Afrilies, Marlia Hafny; Naili, Yuris Tri (Journal of Advanced Health Informatics Research, 2023)
Information Technology that develops rapidly over time has brought significant influence on the way of communicating and the activities of society globally. The health sector is no exception, and the peak is during the Covid-19 pandemic which greatly affects community interactions both individually and with health workers. One of the ways health workers respond to the pandemic period is by utilizing the information technology system optimally to improve the quality of medical services so that people continue to get health services as they should. This article will discuss the development of rules for telemedicine health services in health law in Indonesia, and the extent to which they provide legal protection for health service users and health workers as health care providers. The research method used in this study, namely Normative Juridical Research, is a legal research method carried out by examining library materials or secondary materials. The result of the discussion is legal obligations, which are strengthened by legal sanctions, aiming to realize legal certainty. However, this legal certainty should also consider the expediency of the law so that the law does not only provide legal certainty, but also provides legal benefits, namely the equitable distribution of quality health services to remote parts of the Indonesian state